2005
DOI: 10.1007/s00417-005-0086-4
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity and X-linked color blindness

Abstract: Multi-gene dichromats may benefit from a reduction in chromatic aberration and chromatic noise in the high acuity channel, normally a consequence of combining signals from different cone photoreceptor types and of cone-specific patterns of retinal image defocus and blur. Single-gene dichromats may not share in the advantage because of other molecular differences that influence the development of the retinal mosaic and/or its visual pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…We were underpowered to assess the effects of color vision deficiency as our study only contained 7 individuals; the mean performance of these participants was in line with that of the remainder of the population for both VA and CS tasks. This finding is concordant with recent work demonstrating no expected effect of color vision deficiency [ 56 ], but stands in opposition to older research demonstrating lower light perception thresholds in these individuals [ 57 ]. We do find worse scotopic VA and CS performance in those of Asian ancestry when performing univariate regression analyses, but these associations were no longer statistically significant after accounting for laser eye surgery, task duration, intelligence, and photopic performance.…”
Section: Discussionsupporting
confidence: 87%
“…We were underpowered to assess the effects of color vision deficiency as our study only contained 7 individuals; the mean performance of these participants was in line with that of the remainder of the population for both VA and CS tasks. This finding is concordant with recent work demonstrating no expected effect of color vision deficiency [ 56 ], but stands in opposition to older research demonstrating lower light perception thresholds in these individuals [ 57 ]. We do find worse scotopic VA and CS performance in those of Asian ancestry when performing univariate regression analyses, but these associations were no longer statistically significant after accounting for laser eye surgery, task duration, intelligence, and photopic performance.…”
Section: Discussionsupporting
confidence: 87%
“…This is in agreement with the recent empirical finding that high-acuity luminance vision is not worse in trichromatic female marmosets than in their dichromatic male counterparts, despite the fact that the parvocellular channel of the trichromats also carries the red-green signal (Martin et al, 2011 ). However, a number of studies on human dichromats have reported advantages over trichromats in certain laboratory conditions (Dain and King-Smith, 1981 ; Schwartz, 1994 ; Jägle et al, 2006 ; Sharpe et al, 2006 ; Melin et al, 2007 , 2010 ; Caine et al, 2010 ; Janáky et al, 2014 ), and further research will be required before this question is answered definitively.…”
Section: Discussionmentioning
confidence: 99%
“…Psychophysical experiments comparing trichromats with dichromats that lack either M or L cones would support a trade-off of spatial and colour vision if the trichromats demonstrated inferior luminance vision due to the decorrelation of their M and L cone spectral sensitivities. Dichromats have been shown to have a foraging advantage under certain conditions, such as laboratory experiments (Jägle et al, 2006 ; Janáky et al, 2014 ), low-light (Caine et al, 2010 ), and discovering colour-camouflaged insects (Melin et al, 2007 , 2010 ). However, single-cell recordings from the lateral geniculate nucleus of dichromatic and trichromatic marmosets suggest that the evolution of red-green colour vision has not come at a cost for spatial vision (Martin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The subjective evaluation of these cues may increase the wide range of stereoacuity outcomes we observed in the CCVD patients in our study. Cone differentiation is controlled by competing cone pigment genes, and the mutations of these genes affect the retinal cone mosaic and the postreceptoral wiring [22][23][24][25]. Changes in either the retinal cone mosaic or the postreceptoral wiring may affect the perception of binocular disparity causing variations in the stereoacuity outcomes.…”
Section: Discussionmentioning
confidence: 99%